Surface processing device and method for SiC substrate
Patent Information
- Application Number
- JP2021087582
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-25
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-05-25
Smart Images

Figure 0007632078000001 
Figure 0007632078000002 
Figure 0007632078000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an apparatus and method for processing a surface of a SiC substrate. [Background technology]
[0002] Patent Document 1 provides a polishing method using anodization that can efficiently create a target shape having a scratch-free and damage-free high-quality surface from a difficult-to-machine material such as single crystal SiC. Specifically, the polishing method disclosed in Patent Document 1 includes an anodization process and a polishing process. The anodization process is a process in which a voltage is applied to a workpiece as an anode in the presence of an electrolyte, and a current of a predetermined current density is passed to form an oxide film on the surface of the workpiece. The polishing process is a process in which an oxide film is selectively polished and removed using a polishing material whose Mohs hardness is intermediate between that of the workpiece and the oxide film. The polishing method disclosed in Patent Document 1 performs the anodization process and the polishing process simultaneously to planarize the surface of the workpiece. The technology disclosed in Patent Document 1 is called ECMP. ECMP is an abbreviation for Electro-Chemical Mechanical Polishing. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-92497 A Summary of the Invention [Problem to be solved by the invention]
[0004] For example, the inventors discovered a problem in that in conventional ECMP using a SiC substrate as the workpiece, even if an attempt is made to increase the current density to speed up processing, there is a limit to how much the processing speed can be increased because the oxidation rate in anodization saturates.
[0005] The present invention has been made in consideration of the above-mentioned circumstances, etc. That is, the present invention provides a technique that makes it possible to realize processing characteristics superior to those of the prior art in a surface processing apparatus and a surface processing method for a SiC substrate using, for example, anodization. [Means for solving the problem]
[0006] The surface processing apparatus (1) for a SiC substrate (W) according to claim 1 comprises: a surface processing pad (3) having a grinding layer (32) arranged opposite to the processed surface (W1) of the SiC substrate; Anodizing the workpiece surface that is the object to be processed by the grinding wheel layer; Current density is 10mA / cm 2 That's it a power supply device (5) configured to pass a pulse current having a period exceeding 0.01 seconds and not exceeding 20 seconds through the SiC substrate as an anode in the presence of an electrolytic solution (S); It is equipped with: The method for processing a surface of a SiC substrate (W) according to claim 2 comprises: Current density is 10mA / cm 2 That's it A pulse current having a period of more than 0.01 seconds and not more than 20 seconds is passed through the SiC substrate as an anode in the presence of an electrolytic solution (S), thereby anodizing the processed surface (W1) of the SiC substrate; A surface processing pad (3) having an abrasive layer (32) is disposed so that the abrasive layer faces the surface to be processed, and oxides formed on the surface to be processed by anodization are selectively removed by the abrasive layer.
[0007] In addition, in each section of the application documents, each element may be given a reference symbol in parentheses. In this case, the reference symbol merely indicates an example of the correspondence between the element and the specific configuration described in the embodiment described later. Therefore, the present invention is not limited in any way by the description of the reference symbol. [Brief description of the drawings]
[0008] [Figure 1]1 is a schematic configuration diagram of a surface processing apparatus for carrying out a surface processing method according to an embodiment of the present invention. [Diagram 2] 2A to 2C are diagrams showing a schematic manufacturing process of a SiC wafer that can be realized by using the surface processing apparatus shown in FIG. [Diagram 3] 13 is a graph showing the results of a simulation of the recovery effect of the OH − concentration in a region near the processed surface of a SiC wafer during anodization treatment by pulsing the applied current. [Figure 4] 4 is a graph showing the results of calculation of the total amount of OH- reaction per unit time based on the simulation results shown in FIG. 3. [Diagram 5] 1 is a graph showing the results of an experiment to confirm an improvement in the oxidation rate in anodization by applying a pulsating current. [Figure 6] 1 is a graph showing the relationship between current density and machining speed when a pulse current is applied. [Figure 7] 13 is a graph showing the relationship between current density and machining speed when a constant direct current is applied as a comparative example. [Figure 8] FIG. 13 is a diagram showing the results of evaluating the uniformity of an oxide film on a processed surface when a pulse current is applied. [Figure 9] FIG. 13 is a diagram showing the results of evaluating the uniformity of an oxide film on a processed surface when a direct constant current is applied as a comparative example. [Figure 10] 1 is a graph showing the relationship between the period and the oxidation rate when a pulse current is applied. [Figure 11] 1 is a graph showing the relationship between the duty ratio and the oxidation rate when a pulse current is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (Embodiment) Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that, if various modified examples applicable to one embodiment are inserted in the middle of a series of explanations related to the embodiment, it may hinder understanding of the embodiment. For this reason, the modified examples are not inserted in the middle of a series of explanations related to the embodiment, but are explained together after the series of explanations.
[0010] (Surface processing equipment) 1, the surface processing apparatus 1 according to this embodiment is a processing apparatus for processing a SiC substrate W, which is a single crystal SiC wafer, as a workpiece, and is configured to be capable of performing polishing or grinding using anodization on a workpiece surface W1 of the SiC substrate W. That is, the surface processing apparatus 1 has a configuration as an ECMP apparatus or an ECMG apparatus. ECMG is an abbreviation for Electro-Chemical Mechanical Grinding.
[0011] The surface processing device 1 includes a container 2, a surface processing pad 3, a driving device 4, and a power supply device 5. In this embodiment, the container 2 is configured to be capable of housing the SiC substrate W while immersing it in an electrolytic solution S that does not contain an etchant component. The etchant component is a component (e.g., hydrofluoric acid, etc.) that constitutes a dissolving solution capable of dissolving an oxide film (i.e., a SiC oxide formed in a film shape) formed on the processing surface W1 by anodization. The electrolytic solution S is, for example, an aqueous solution of sodium chloride, potassium chloride, sodium nitrate, etc.
[0012] The surface processing pad 3 has an electrode 31 and a grinding layer 32. The electrode 31 is a plate-shaped member made of a good conductor such as metal, and is formed of, for example, a copper plate. The grinding layer 32 is bonded to the electrode 31. That is, the surface processing pad 3 has a configuration in which the electrode 31 and the grinding layer 32 are bonded in the thickness direction of the surface processing pad 3. The grinding layer 32 has a polishing material having a Mohs hardness intermediate between that of single crystal SiC and its oxide film. That is, the grinding layer 32 is configured to be able to selectively polish or remove the oxide film generated on the processing surface W1 by anodization by being rotated by the driving device 4 while being disposed opposite to the processing surface W1 of the SiC substrate W. In this embodiment, the surface processing pad 3 is provided such that the grinding layer 32 is disposed opposite to the processing surface W1 of the SiC substrate W with the electrolyte S sandwiched therebetween.
[0013] The driving device 4 is configured to rotate the surface processing pad 3 around a predetermined rotation axis parallel to the thickness direction, and to relatively move the SiC substrate W and the surface processing pad 3 in an in-plane direction perpendicular to the rotation axis. The power supply device 5 is configured to apply a voltage in the presence of the electrolytic solution S to the SiC substrate W as the workpiece as an anode and to the electrode 31 in the surface processing pad 3 as a cathode, thereby passing a current for anodizing the workpiece surface W1 to be processed by the grinding stone layer 32. In this embodiment, the power supply device 5 is provided to apply a pulse current having a period of more than 0.01 seconds and not more than 20 seconds (i.e., to pass between the SiC substrate W and the electrode 31).
[0014] (Outline of the surface processing method according to the embodiment) The surface processing apparatus 1 according to this embodiment is configured to be capable of performing a surface processing method (i.e., a polishing method or a grinding method) for a SiC substrate W, which includes the processes described below, in order to realize processing characteristics (e.g., processing speed or flatness) superior to those of conventional ECMP. Note that the anodization in (2) and the selective removal of the oxide film in (3) can be performed simultaneously or sequentially. (1) The surface processing pad 3 is disposed opposite to the processing surface W1 of the SiC substrate W with the electrolytic solution S therebetween. (2) A pulse current having a period exceeding 0.01 seconds and not exceeding 20 seconds is passed through the SiC substrate W as an anode in the presence of the electrolyte S, thereby anodizing the workpiece surface W1 to be processed by the grinding layer 32. (3) The workpiece surface W1, which has been anodized by application of a pulse current, is ground or polished by the grinding layer 32, thereby selectively removing the oxide film (i.e., the oxide formed in a film form) on the workpiece surface W1.
[0015] A to C in Fig. 2 are schematic diagrams showing the manufacturing process of a SiC wafer, i.e., a SiC substrate W, using the surface processing apparatus 1 shown in Fig. 1. Note that a conventional manufacturing method P shown in Fig. 2 as a comparative example shows schematic manufacturing processes of a SiC wafer when a well-known CMP is used instead of the ECMP or ECMG by the surface processing apparatus 1 shown in Fig. 1. CMP is an abbreviation for Chemical Mechanical Polishing.
[0016] First, an outline of the conventional manufacturing method P will be described. The conventional manufacturing method P includes, in this order, an ingot forming step, a slicing step, a wafer grinding step, a rough CMP step, and a finish CMP step. The ingot forming step is a step of processing a crystal-grown block of single crystal SiC into a cylindrical ingot. The slicing step is a step of obtaining a SiC substrate W, which is a thin disk-shaped SiC wafer, from the ingot by wire slicing. The wafer grinding step is a step of flattening the SiC substrate W by removing the "waviness" generated in the SiC substrate W in the slicing step by grinding. The rough CMP step and the finish CMP step are steps of processing the processed surface W1 of the SiC substrate W into a mirror surface, which is a surface state preferable for the semiconductor device manufacturing process.
[0017] Generally, in a wafer grinding process, a "damage layer" having a certain degree of "subsurface damage" is formed on the processing surface W1 of the SiC substrate W and its neighboring portions. The "subsurface damage" is, for example, cracks, residual stress, etc. Therefore, first, the processing surface W1 is mirror-finished by a rough CMP process. Then, the damage layer is removed by the subsequent finish CMP process.
[0018] As disclosed in Patent Document 1, ECMP, which is a damage-free polishing process, can achieve a processing speed higher than that of CMP. Therefore, by replacing the CMP process with the ECMP process, high-speed and damage-free polishing of the workpiece surface W1 can be realized. In the ECMP process, a soft grindstone containing relatively soft abrasive grains (e.g., ceria abrasive grains, etc.) is used as the grindstone layer 32.
[0019] 2, the rough CMP step in the conventional manufacturing method P can be replaced with a rough ECMP step, and the finish CMP step in the conventional manufacturing method P can be replaced with a finish ECMP step. This makes it possible to reduce the manufacturing cost by about 40% compared to the conventional manufacturing method P.
[0020] In addition, the ECMG process can be realized by using a hard grindstone containing relatively hard abrasive grains (such as diamond grains) as the grindstone layer 32. That is, as in the manufacturing method B shown in Fig. 2, the wafer grinding process in the conventional manufacturing method P can be replaced with the ECMG process. This makes it possible to reduce the manufacturing cost by about 20% compared to the conventional manufacturing method P.
[0021] Here, the ECMG process, which is a low-damage grinding process, reduces the occurrence of subsurface damage compared to the wafer grinding process in conventional manufacturing method P. Therefore, when the wafer grinding process in conventional manufacturing method P is replaced with the ECMG process, it is also possible to transform manufacturing method B into manufacturing method C. In manufacturing method C, the rough CMP process in conventional manufacturing method P is omitted, and the finish CMP process in conventional manufacturing method P is replaced with a finish ECMP process. This makes it possible to reduce the manufacturing cost by almost half compared to conventional manufacturing method P.
[0022] (Improvement of oxidation rate by current pulsing) The inventors have found that in conventional ECMP for processing SiC substrates, even if an attempt is made to increase the current density to increase the processing speed, the oxidation rate in the anodic oxidation reaches saturation, limiting the improvement of the processing speed. According to the inventors' investigations, the reason for the saturation of the increase in the oxidation rate with an increase in the current density is the increase in the reactive species, i.e., OH, in the electrolyte S in the area near the processing surface W1. - The reason for this is believed to be a shortage of the supply of the material. The region near the work surface W1 is hereinafter referred to as the "surface vicinity region."
[0023] Specifically, OH is formed in the near-surface region by anodization. - is consumed, and OH - The concentration decreases. Then, OH - is supplied to the near-surface region from the bulk region of the electrolyte S, that is, from a region farther from the workpiece surface W1 than the near-surface region, according to the principle of material diffusion. - The concentration decreases as it approaches the processed surface W1 according to Fick's law.
[0024] OH in the near-surface region - Whether the supply of OH is sufficient or not depends on the oxidation rate, i.e. - The consumption rate of OH from the bulk region - In the conventional ECMP, the current conditions for anodization are direct and constant, and the OH - The supply rate of OH in the near-surface region is insufficient. - There will be a supply shortage.
[0025] Therefore, the inventors applied a pulsed current for anodization having an on-time and an off-time, and during the off-time, OH was transferred from the bulk region to the near-surface region. - supplying OH in the near-surface region -It was found that the oxidation rate can be improved by recovering the concentration. Here, the "off time" refers to the time during which the current is substantially zero. It was also found that by making the off time relatively short (specifically, for example, about 0.01 to 10 seconds), it is possible to effectively avoid an increase in the total processing time while maintaining a good oxidation rate during the on time.
[0026] FIG. 3 shows the effect of providing an off time for the anodizing current on the OH - 1 shows the results of a computer simulation showing the effect of recovering the concentration. Here, "anodic oxidation current" refers to the applied current for anodization, that is, the current flowing from the power supply device 5 to the SiC substrate W that is actually used for anodization of the work surface W1, not for electrolysis of the electrolyte S. In the figure, "Toff" on the horizontal axis indicates the length of the off time. The vertical axis shows the concentration recovery effect of the work surface W1 at a position 10 μm away from the flat surface, assuming that the work surface W1 is a flat surface. - The preconditions for the simulation are as follows: Diffusion coefficient D = 1.9 × 10 -9 m 2 / s Bulk region OH - Concentration C=6.02×10 17 pieces / cm 3
[0027] Figure 4 shows the OH per unit time based on the simulation results shown in Figure 3. - The results of the calculation of the total reaction amount are shown. The horizontal solid line in the figure indicates the case of Toff = 0, i.e., direct current and constant current. Note that "direct current and constant current" will be abbreviated to simply "constant current" hereinafter.
[0028] As is clear from Figs. 3 and 4, by using a pulsed anodizing current with an off time of 0.01 seconds or more, the OH in the near-surface region can be reduced. - Specifically, the inventors have found that, as shown in Figs. 3 and 4, when the off time is between 0.01 seconds and 10 seconds, the supply of OH is effectively reduced in the near-surface region. -Simulations have confirmed that it is possible to supply OH by providing off time. - The effect of restoring the concentration tends to saturate in the region where Toff is relatively long, so it is considered more preferable that the off time is about 0.1 to 1 second.
[0029] Therefore, the inventors conducted an experiment using a 30 mm square wafer to confirm the difference in oxidation rate in anodization between constant current application and pulse current application. The pulse current was a square wave with an on-time of 1 second and an off-time of 1 second (i.e., a period of 2 seconds and a duty ratio of 0.5). After anodization, the oxide film was removed with hydrofluoric acid, and the oxidation rate was calculated from the amount removed. The experimental results are shown in Figure 5. In Figure 5, the circular plots show the case of a pulse current, and the diamond plots show the case of a constant current. The current density value in the case of a pulse current is the value during the on-time.
[0030] As is clear from Figure 5, in the case of a constant current of 10 mA / cm 2 Even at current densities as high as this, a high oxidation rate cannot be obtained. In contrast, when a pulse current is applied, a high oxidation rate is obtained in the low to high current density range. As the current density increases, the oxidation rate also increases. Therefore, when a pulse current is applied, the current density can be increased to increase the processing speed. In particular, the application of a high current density increases the amount of OH in the near-surface region. - Even if a large amount of OH is consumed, the OH - Therefore, the application of a pulse current is expected to realize high-speed machining by applying a current with a high current density.
[0031] (Improved machining speed by current pulsing) The processing speed is affected not only by the oxidation speed, but also by the properties of the oxide film. Specifically, in conventional ECMP, a constant current with a relatively low current density was applied to form an oxide film with a relatively high density and hardness. When the composition of the oxide film formed by applying a constant current corresponding to conventional ECMP was analyzed using an XPS device, it was found to contain approximately 40% SiOC, approximately 30% SiO, and approximately 10% Si2O3. XPS stands for X-ray Photoelectron Spectroscopy.
[0032] In contrast, when the composition of the oxide film formed by applying a pulse current was analyzed by an XPS device, the SiOC content was significantly lower than that of the oxide film formed by applying a constant current, while the SiO content was significantly higher. In addition, when a transmission electron microscope image of the cross section was confirmed, the generation of an internal void layer was more prominent in the oxide film formed by applying a pulse current than in the oxide film formed by applying a constant current. In addition, a tendency for the amount of voids in the void layer to increase was observed by increasing the pulse period. Specifically, under the condition of a duty ratio of 0.5, even when the period was 0.02 seconds, the generation of the void layer was more prominent than in the case of a constant current, and the amount of voids increased with each increase in the period from 0.1 seconds to 1 second. That is, the inventor confirmed that an oxide film that has a relatively low density and can be easily polished or ground is formed in the period range of 0.02 to 1 second.
[0033] Considering the above results, the following effects can be considered as the effects of applying a pulse current. -The anodization of SiC is promoted by an adequate supply of SiO, which is more oxidized than SiOC, and more SiO is generated, which is more oxidized than SiOC. As the degree of oxidation progresses in the order of SiOC and SiO, the expansion coefficient increases, and the generation of voids due to internal stress in the oxide film is promoted. For this reason, the generation of more SiO makes the generation of a void layer caused by the difference in the expansion coefficient before and after oxidation more pronounced. In this way, an oxide film that contains a lot of SiO and has an increased amount of voids in the void layer has a lower hardness, which improves the grinding or polishing speed. Furthermore, when a large number of cracks occur on the surface of the oxide film due to the generation of voids, the reactive species OH - The anodization can be further accelerated by the penetration of the impurities from the cracks into the film. Thus, the effect of applying a pulsating current is expected to be an improvement in the polishing rate.
[0034] 6 and 7 show the results of comparing the effect of increasing the polishing rate when the current density is increased between the application of a pulse current and the application of a constant current. That is, FIG. 6 shows the relationship between the current density and the polishing rate when the current density is changed when the pulse current is applied. The pulse current has a period of 2 seconds and a duty ratio of 0.75. FIG. 7 shows the relationship between the current density and the polishing rate when the current density is changed when the constant current is applied. A 4-inch wafer was used as the object to be polished. The polishing rate was calculated as follows: the change in thickness of the wafer before and after polishing was measured at nine points, including a position near the center, at approximately equal intervals on a line passing through the center of the surface of the 4-inch wafer as a sample, and the average thickness change amount within a unit time at the nine measurement points was calculated to determine the polishing rate of the wafer.
[0035] As shown in Figure 7, when a constant current was applied, 15 mA / cm 2 In the current density range below, the polishing rate increases with increasing current density. However, in the range below 20 mA / cm 2 In the above current density region, the current density is 10 to 15 mA / cm 2 The polishing rate was lower than that of 5 mA / cm 2In contrast, as shown in FIG. 6, when a pulse current was applied, the polishing rate was about the same as that in the low current region of 40 mA / cm 2 It was confirmed that even in the above-mentioned large current region, the polishing rate increases with an increase in current density.
[0036] (Improved flatness due to current pulsing) As mentioned above, when a constant current is applied, the OH - It is difficult to recover the concentration. Therefore, as the formation of the oxide film progresses, it becomes difficult to maintain the anodic oxidation current. 2 Even if a certain voltage is applied to pass a large constant current exceeding 10 mA / cm, the current value rises rapidly to a peak value corresponding to the target value and then immediately drops rapidly. 2 Even under the current application conditions below, which are considered to enable relatively stable anodization, a part of the current is used for electrolysis of the electrolyte S rather than for anodization. Furthermore, the ratio of the current used for anodization to the current used for electrolysis also varies depending on the amount of OH in the near-surface region. - Fluctuations in the anodization current cause the uniformity of the oxide film to be formed to be impaired.
[0037] On the other hand, when a pulsed current is applied, the anodizing current can be well maintained. The inventors have confirmed that an extremely good current maintenance effect can be obtained, particularly when the cycle is 0.1 seconds or more. In this way, the anodizing current is stably maintained by pulsing the applied current, which can improve the uniformity of the oxide film and is expected to improve the flatness, i.e., the TTV. TTV is an abbreviation for Total Thickness Variation.
[0038] Figure 8 shows the evaluation results of the uniformity of the oxide film when a pulse current was applied. Figure 9 shows the evaluation results of the uniformity of the oxide film when a constant current was applied as a comparative example. The current application conditions are as follows. Constant current: Voltage 50V (i.e. current density 20mA / cm 2 equivalent), current application for 40 minutes Pulse current: Voltage 50V (i.e. current density 20mA / cm 2 equivalent), period 0.5 seconds, duty ratio 0.5, current application 20 minutes
[0039] The evaluation method is as follows. A first masking tape is applied in a straight line on the wafer surface before anodization so that it passes through the center of the wafer. Next, a second masking tape is applied in a straight line so that it passes through the center of the wafer and is perpendicular to the first masking tape. In this manner, with the two masking tapes applied in a roughly "X" shape so that they are perpendicular to each other on the wafer surface before anodization, the wafer surface is anodized.
[0040] No oxide film is formed by anodization in the area where the masking tape was attached. Therefore, when the masking tape is peeled off after anodization, a step is created between the area where the masking tape was attached and the adjacent area due to the presence or absence of the oxide film. By measuring the height of this step at multiple points, it is possible to evaluate the uniformity of the thickness of the oxide film.
[0041] The unoxidized portion corresponding to the portion where the first masking tape is applied is called the "first line", and the unoxidized portion corresponding to the portion where the second masking tape is applied is called the "second line". The height of the step is measured at 14 equally spaced points on each of the first and second lines. In Figs. 8 and 9, the numbers 1 to 14 on the horizontal axis indicate the measurement points on the lines. The diamond plots indicate the measurement results on the first line, and the circle plots indicate the measurement results on the second line. As is clear from Figs. 8 and 9, the application of the pulse current improved the uniformity of the thickness of the oxide film. The application of the pulse current also achieved a flatness after polishing of TTV=1.756 μm.
[0042] (Pulse period) Fig. 10 shows the change in oxidation rate when the period of the pulse current is changed. In the figure, the vertical axis indicates the oxidation rate, and the horizontal axis T indicates the period. The horizontal solid line in the figure indicates the value in the case of a constant current as a comparative example.
[0043] The evaluation conditions were as follows. A 4-inch wafer was used as the sample. In order to match the amount of charge between the current application conditions, the duty, current density, and application time were the same. The duty ratio was 0.5, and the current density was 20 mA / cm. 2 It was decided.
[0044] As is clear from FIG. 10, a higher oxidation rate than that of the constant current was obtained at a period in the range of at least 0.01 to 20 seconds. - In order to recover the concentration, it is necessary to provide an off time of 0.01 seconds or more. Therefore, the cycle that provides a good oxidation rate is longer than 0.01 seconds and shorter than 20 seconds. In particular, when the cycle is 0.01 seconds, the off time is 0.005 seconds, so the oxidation rate is only slightly higher than that in the case of constant current. Therefore, for example, when the off time is the minimum value of 0.01 seconds, if the duty ratio is 0.25 to 0.75 as described below, the minimum value of the suitable cycle is about 0.02 seconds.
[0045] As described above, in consideration of the ease of processing due to the formation of a low-density oxide film, the period is preferably in the range of 0.02 to 1 second. Furthermore, as shown in FIG. 10, in the region where the period exceeds 20 seconds, the oxidation rate is only slightly higher than that in the case of a constant current. The reason for this is considered to be that while the effect of improving the oxidation rate by providing an off time saturates as described above, the overall cycle time becomes longer. Therefore, in consideration of the simulation results shown in FIG. 3 and FIG. 4, the evaluation results of the actual oxidation rate shown in FIG. 10, and the cycle time in the actual manufacturing process, the period is preferably 0.1 seconds or more and 2 seconds or less.
[0046] Considering all of the above points, the period is preferably 0.02 to 2 seconds, more preferably 0.02 to 2 seconds, even more preferably 0.02 to 1 second or 0.1 to 2 seconds, and most preferably 0.1 to 1 second.
[0047] (duty ratio) Fig. 11 shows the change in oxidation rate when the duty ratio of the pulse current is changed. In the figure, the vertical axis indicates the oxidation rate, and the horizontal axis indicates the duty ratio. The horizontal solid line in the figure indicates the value in the case of a constant current as a comparative example.
[0048] The evaluation conditions were as follows. A 4-inch wafer was used as a sample. In order to match the amount of charge between the current application conditions, the current density was the same (i.e., 20 mA / cm 2 ) and the application time was adjusted so that the product of the duty ratio and the application time was constant. As shown in Fig. 11, by setting the duty ratio to 0.25 to 0.75, a good oxidation rate, higher than that of a constant current, was obtained.
[0049] (Summary of the effects of current pulsing) As described above, by pulsing the applied current in the anodic oxidation, not only can the oxidation rate be increased, but also the density and hardness of the oxide film can be reduced, making it easier to polish or grind, and the uniformity of the oxide film can be improved, resulting in improved flatness. This can effectively increase the polishing or grinding speed, and thereby reduce the wafer manufacturing cost.
[0050] Regarding the wafer size, even if the diameter is increased from 4 inches as in the above example, it is possible to obtain the same polishing speed. Specifically, the surface processing method according to the present embodiment can be suitably applied to wafer sizes of, for example, 1 to 8 inches.
[0051] (Modification) The present invention is not limited to the above embodiment. Therefore, the above embodiment can be modified as appropriate. Representative modified examples will be described below. In the following description of the modified examples, differences from the above embodiment will be mainly described. In addition, the same reference numerals are used for parts that are the same or equivalent to each other in the above embodiment and the modified examples. Therefore, in the following description of the modified examples, the description of the above embodiment can be appropriately used for components having the same reference numerals as the above embodiment, unless there is a technical contradiction or special additional explanation.
[0052] The present invention is not limited to the specific device configurations shown in the above embodiments. That is, Fig. 1 is a simplified schematic diagram for simply explaining the outline of the surface processing device 1 according to the present invention and the surface processing method that can be implemented by the surface processing device 1. Therefore, the configuration of the surface processing device 1 that is actually manufactured and sold does not necessarily match the exemplary configuration shown in Fig. 1. In addition, the configuration of the surface processing device 1 that is actually manufactured and sold may be appropriately changed from the exemplary configuration shown in Fig. 1.
[0053] For example, the configuration of the surface processing pad 3 is not limited to the specific device configuration shown in the above embodiment. Specifically, the electrode 31 and the grindstone layer 32 may not be bonded in the thickness direction of the surface processing pad 3. More specifically, for example, the electrode 31 and the grindstone layer 32 may be adjacently arranged in an in-plane direction perpendicular to the thickness direction of the surface processing pad 3. That is, the surface processing device 1 may be configured so that the electrode 31 and the surface processing pad 3 alternately face a specific part of the surface W1 to be processed by rotating or moving the surface processing pad 3. Alternatively, the electrode 31 may be separate from the surface processing pad 3. That is, the surface processing device 1 may be configured so that the electrode 31 and the surface processing pad 3 alternately face the entire surface W1 or a specific part of the surface W1 to be processed. There is also no particular limitation on the type of abrasive grains contained in the grindstone layer 32.
[0054] The electrolyte S may contain an etchant component. That is, the surface processing apparatus 1 according to the present invention and the surface processing method that can be implemented by the same may selectively remove an oxide film formed by anodization using both the etchant and the surface processing pad 3, thereby polishing or grinding the workpiece surface W1.
[0055] The surface processing apparatus 1 according to the present invention and the surface processing method that can be implemented by the apparatus are typically applicable to any of the ECMG process, the rough ECMP process, and the finish ECMP process in the manufacturing methods A to C shown in Fig. 2. However, for example, in the manufacturing method A, the processed surface W1 after the rough ECMP process is expected to be well mirror-finished and to have almost no subsurface damage caused by the rough ECMP process. Therefore, for the finish ECMP process, it is possible to use the conventional ECMP by applying a constant current.
[0056] Needless to say, the elements constituting the above-mentioned embodiment are not necessarily essential, except when expressly stated as essential or when considered to be obviously essential in principle. Furthermore, when the numbers, amounts, ranges, etc. of the components are mentioned, the present invention is not limited to the specific values, except when expressly stated as essential or when clearly limited to a specific value in principle. Similarly, when the shapes, directions, positional relationships, etc. of the components are mentioned, the present invention is not limited to the shapes, directions, positional relationships, etc., except when expressly stated as essential or when clearly limited to a specific shape, direction, positional relationship, etc. in principle.
[0057] The modified examples are not limited to the above examples. That is, for example, other than those exemplified above, multiple embodiments may be combined with each other as long as there is no technical contradiction. Similarly, multiple modified examples may be combined with each other as long as there is no technical contradiction. [Explanation of symbols]
[0058] 1 Surface processing equipment 2 containers 3 Surface treatment pad 31 electrode 32 Grindstone layer 4. Drive unit 5 Power supply S Electrolyte W-SiC substrate W1 Work surface
Claims
1. A surface processing apparatus (1) for a SiC substrate (W), comprising: A surface processing pad (3) having a grinding stone layer (32) arranged opposite to the processed surface (W1) of the SiC substrate; a power supply unit (5) configured to pass a pulse current having a current density of 10 mA / cm 2 or more and a period of more than 0.01 seconds and not more than 20 seconds through the SiC substrate as an anode in the presence of an electrolytic solution (S) for anodizing the work surface that is the object to be processed by the grinding stone layer; A surface processing device comprising:
2. A method for processing a surface of a SiC substrate (W), comprising the steps of: a pulse current having a current density of 10 mA / cm 2 or more and a period of more than 0.01 seconds and not more than 20 seconds is passed through the SiC substrate as an anode in the presence of an electrolytic solution (S), thereby anodizing the processed surface (W1) of the SiC substrate; a surface processing pad (3) having a grinding layer (32) is disposed so that the grinding layer faces the work surface, and oxides generated on the work surface by anodization are selectively removed by the grinding layer; Surface treatment method.
3. The pulse current has an off time and an on time, and the off time is not less than 0.01 seconds and not more than 10 seconds. The surface processing method according to claim 2.
4. The period is 0.02 to 1 second. The surface treatment method according to claim 2 or 3.
5. The period is 0.1 seconds or more. The surface processing method according to any one of claims 2 to 4.
6. Anodizing the work surface and selectively removing the oxide formed on the work surface by the grindstone layer are performed simultaneously or sequentially. The surface processing method according to any one of claims 2 to 5.
7. The grinding stone layer grinds or polishes the workpiece surface that has been anodized by application of the pulse current. The surface processing method according to claim 6.
Citation Information
Patent Citations
Anodic oxidation assisted shape creation etching method, polishing method and high-precision shape creation method
JP2014187131A
Polishing method using anode oxidation
JP2017092497A
Flattening treatment method of silicon wafer
JP2018141188A
Polishing method with anodizing
JP2021027359A
Silicon carbide monocrystal substrate and manufacturing method therefor
WO2010090024A1